Clinical Assessments and EEG Analyses of Encephalopathies Associated With Dynamin-1 Mutation - Li, Hua; Fang, Fang; Xu, Manting; Liu, Zhimei; Zhou, Ji; Wang, Xiaohui; Wang, Xiaofei; Han, Tongli (Frontiers in Pharmacology, 2019)
Objective To investigate clinical and electroencephalographic features of children with Dynamin-1 (DNM1) gene mutation-related epileptic encephalopathies. Methods Data of a patient with diagnosed Is caused by DNM1 gene mutation in March 2017(The first diagnosis was made in the Department of Neurology, Beijing Children's Hospital Affiliated to Capital Medical University in July 2016) was analyzed, and “Dynamin-1” “DNMl” was used the search terms to refer to clinical materials from relevant literature as October 2018 from China Knowledge Network database, Wanfang database, online human Mendelian genetic database and PubMed database for summarizing. Results Among 24 children patients, there were 18 male patients and 6 female patients. The age of onset was 3 weeks to 13 months after birth. Among twenty-three (95.8%) patients with abnormal EEG results, there was only one case of non-specific background activity slackened, 13 (56.5%) case of epileptiform discharge and background activity slackened, and 13 (56.5%) cases of multifocal discharge; 2 cases of hypsarrhythmia (8.7%). Other epileptiform discharges: 6 (26.1%) cases of slow-spike wave complex, 5 (21.7%) cases of fast-wave activity, 7 (30.4%) cases of extensive spike activity and 4 (17.4 %) cases of focal epileptiform discharge. Besides, there were multi-focal discharge or hypsarrhythmia, and 5 cases (21.7%) of slow-spike and slow wave complex. For 24 cases of children epileptic encephalopathies caused by DNM1 mutations have reported 15 DNM1 gene mutation sites, of which c.709C>T (P.Ar9237Trp) was the most common. After 24 children patients underwent therapy with multiple antiepileptic drugs, 3 cases of epileptic seizure were controlled but 19 cases were uncontrolled. Conclusion Electroencephalogram manifestations of epileptic encephalopathies related to DNM1 gene mutation is consistent with change in the EEG of general epileptic encephalopathies, and characteristics of EEG can be gradually evolved and characterized. When the brain discharge was severely abnormal in the early stage, the evolution and improvement of EEG characteristics were unobvious. Multiple anti-epileptic drugs feature in poor long-term efficacy and poor prognosis.